PENGARUH PEMBERIAN AIR PANAS PADA PEMBUATAN MORTAR GEOPOLIMER BERBASIS SEMEN GEOPOLIMER - Maryani, Evi; Firdaus, Firdaus (Ensiklopedia of Journal, 2024)
: Geopolymer mortar is a mortar whose binder consists of natural ingredients. The natural material of geopolymer mortar has a high content of oxides, silicates and aluminum. The resulting geopolymer mortar completely replaces portland cement with fly ash. The fly ash used must be activated with an alkane solution in the form of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) as a catalyst to increase the polymerization reaction. The aim of this research is to analyze the effect of providing hot water on the manufacture of geopolymer mortar based on geopolymer cement. Where this research used a cube mold measuring 5cm×5cm×5cm with 27 test objects, the results of this research showed that the effect of giving hot water was very influential on the compressive strength value at the age of 7 days, 14 days and 28 days with variations in hot water temperature of 50oC , 60oC, 70oC. Hot water temperature greatly influences the compressive strength value of geopolymer mortar at 7 days, 14 days and 28 days. The higher the hot water temperature, the higher the compressive strength value due to the increase in the hydration reaction rate between the hot water temperatures. Temperature 70oC aged 7 days, 14 days, 28 days, the highest compressive strength values are around 15.2 MPa, 15.73 MPa, 16.13 MPa.Keywords : Mortar, Hot Water, Fly Ash, Temperature, Compressive Strength